Occupational prestige and occupational social value in the United Kingdom: New indices for the modern British economy - Newlands, Gemma; Lutz, Christoph (Research in social stratification and mobility, 2024)
Sociological research has long been interested in occupational evaluation. However, occupational research remains hampered by conceptual ambiguity and methodological problems. To address these issues, we present new indices of occupational prestige and occupational social value for 576 occupation titles aligned with the ILO International Standard Classification of Occupations (ISCO-08). A shorter core list with 130 occupation titles – one per ISCO-08 minor group – is also provided. Based on comprehensive and recent evidence from 2429 respondents, we carve out the evaluative landscape of occupations in the United Kingdom. We show how occupational prestige and occupational social value are correlated but distinct. A clear hierarchy appears, with highly educated occupations at the top and stigmatised or illicit occupations at the bottom. The study thus contributes to social stratification research and encourages reuse of the scores in future occupational research. ●Occupational prestige and occupational social value are distinct evaluation axes.●A new, comprehensive and modern list of 580 occupation titles is developed.●The occupation titles are aligned with ISCO-08, advancing occupational research.●Healthcare occupations score particularly high in terms of social value.●Many digital economy occupations suffer from a perceived social value deficit.